2022
DOI: 10.1002/icd.2354
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depressive symptoms and early childhood temperament before and during the COVID‐19 pandemic in the United Kingdom

Abstract: The COVID-19 pandemic is an unexpected and major global event, with the potential to have many and varied impacts on child development. However, the implications of the pandemic for maternal depressive symptoms, early childhood temperament dimensions, and their associations, remain largely unknown. To investigate this, questionnaires were completed by mothers (N = 175) before and during the pandemic when their child was 10-and 16-months old (Study 1), and by an extended group of mothers with young children (6-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Our own previous findings from this sample, based on questionnaire data alone [ 44 ], showed cascading associations between maternal depressive symptoms and infant negative affect across the first year of life, and primarily during the first 6 months of life, with most of these effects being maternally driven (i.e., earlier maternal depression predicted later infant negative affect, but not the other way round). Other previous studies have also found that infants of depressed mothers are characterized by more negative affect [e.g., 60 , 63 , 64 ], and a recent study replicated the association between maternal depression and infant negative affect at 10 months, whereas this association had disappeared by 16 months [ 65 ]. Thus, this specific association between maternal depressive symptoms and the construct of infant negative affect might be stronger in early infancy and start weakening by the end of the first year of life.…”
Section: Discussionmentioning
confidence: 71%
“…Our own previous findings from this sample, based on questionnaire data alone [ 44 ], showed cascading associations between maternal depressive symptoms and infant negative affect across the first year of life, and primarily during the first 6 months of life, with most of these effects being maternally driven (i.e., earlier maternal depression predicted later infant negative affect, but not the other way round). Other previous studies have also found that infants of depressed mothers are characterized by more negative affect [e.g., 60 , 63 , 64 ], and a recent study replicated the association between maternal depression and infant negative affect at 10 months, whereas this association had disappeared by 16 months [ 65 ]. Thus, this specific association between maternal depressive symptoms and the construct of infant negative affect might be stronger in early infancy and start weakening by the end of the first year of life.…”
Section: Discussionmentioning
confidence: 71%
“…Seventh, this study was conducted before the pandemic. Though temperament traits were broadly considered to be highly stable across time and that COVID-19 infections did not biologically affect early temperament development [ 106 ], this may nonetheless limit the applicability of our findings. For instance, stress and life disruptions associated with maternal COVID-19 infections may still result in maternal-rated changes in infant temperament at 6 months [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Child temperament has also been associated with parental depression (Tolja, Radoš, & Andelinović, 2020) during COVID-19 (Fiske, Scerif, & Holmboe, 2022). However, there is limited research on the associations between children's temperament across maternal mental health symptoms (i.e., stress and anxiety) during COVID-19.…”
Section: Impacts Of Covid-19 On Maternal Mental Healthmentioning
confidence: 99%